A Transition to Sustainable Housing Progress and Prospects for a Low Carbon Housing Future - Moore, Trivess (Springer Nature, 2023)
This open access book explores the environmental, social, and financial challenges of housing provision, and the urgent need for a sustainable housing transition. The authors explore how market failures have impacted the scaling up of sustainable housing and the various policy attempts to address this. Going beyond an environmental focus, the book explores a range of housing-related challenges including social justice and equity issues. Sustainability transitions theory is presented as a framework to help facilitate a sustainable housing transition and a range of contemporary case studies are explored on issues including high performing housing, small housing, shared housing, neighbourhood-scale housing, circular housing, and innovative financing for housing. It is an important new resource that challenges policy makers, planners, housing construction industry stakeholders, and researchers to rethink what housing is, how we design and construct it, and how we can better integrate impacts on households to wider policy development.